Attitude System in Donald Trump’s Speech on Harvard’s Foreign Students: An Appraisal Analysis - Cut Nadia Muji Rahmah; Nurlela; Nidiya Mawarni; Aisyah Inka Putri Lubis (LingPoet: Journal of Linguistics and Literary Research, 2026)
This study investigates the evaluative language used by Donald Trump in his speech concerning Harvard University’s treatment of foreign students, employing the Attitude system from Appraisal Theory. Focusing on three subsystems such as Affect, Judgement, and Appreciation. This study analyzes how Trump constructs his political persona, positions ideological others, and frames educational policy within nationalist discourse. The data were drawn from transcribed segments of a publicly available speech and analyzed qualitatively using Appraisal Theory as the primary analytical framework. The findings reveal that Judgement was the most dominant Attitude type (44.29%), followed by Appreciation (35.71%) and Affect (20%). Most evaluations (58.57%) were directed toward others (especially institutions and political actors), while the remaining 41.43% targeted the speaker himself. The overall evaluative polarity was predominantly negative (61.43%), with positive evaluations accounting for 38.57% of the data. Trump frequently praised his own leadership capacity while expressing dissatisfaction or moral condemnation toward elite institutions. Notably, this study highlights a rarely examined theme in Trump’s discourse: education policy. By framing foreign students as victims and elite universities as ideologically flawed, Trump repositions the education sector as a site of political contestation. This study contributes to the growing body of literature on political discourse by extending Appraisal analysis into the educational domain, revealing how evaluative meanings shape public narratives beyond traditional themes like war and immigration.